Motivation and self-enhancement as antecedents of implicit theories in youth sport. (October 2021) - Warburton, Victoria E.; Spray, Christopher M.; Bishop, Krystal C.M.; Maloney, Ciaran M.C.
Abstract: We explored motivation, and specifically the motivation to see oneself in a positive light, as an antecedent of implicit theory endorsement in two youth sport contexts. Data from two studies that represent four samples are reported. We provide the first evidence of an antecedent of implicit theories in the physical domain and show that young people's implicit theories may be shaped by motivation and self-enhancement. In both contexts, we found that strengths were viewed as more malleable than their weaknesses, and that these differences disappeared when considering the same attributes in others. Moreover, in one context, we showed that desire to change a perceived weakness may act as a self-protective motive against the potentially negative effects of beliefs about its stability. The current study enhances our understanding of how implicit theories may be shaped in young people through identifying internal factors that promote the endorsement of these important motivational constructs. Highlights: Young people's implicit theories can be shaped by internal factors. Motivation and self-enhancement were antecedents of implicit theories. Motivated implicit theories are used as a self-enhancement strategy in youth sport.